Initial Extracorporeal Shockwave Lithotripsy versus Ureteroscopy: A Re-treatment and Cost Analysis Using a Longitudinal, Population-Based Database. Issue 2 (28th March 2021) - Patel, Parth M.; Koehne, Elizabeth; Chen, Victor S.; Nelson, Marc; Baker, Marshall; Gupta, Gopal; Baldea, Kristin G.
Abstract: Introduction: We sought to compare re-treatment rates between shockwave lithotripsy and ureteroscopy to evaluate the effectiveness of these modalities. Additionally, we aimed to compare costs associated with re-treatment. Methods: The Healthcare Cost and Utilization Project State Ambulatory Surgery Database for Florida from 2009 to 2015 was used to identify patients who underwent shockwave lithotripsy or ureteroscopy. Patients were tracked for subsequent stone surgeries within 3 months, 6 months and 1 year. Costs of care were estimated and descriptive analyses were performed. A multivariable logistic regression model was used to determine predictors of a second procedure. Results: A total of 98, 011 patients underwent initial shockwave lithotripsy or ureteroscopy. Of those who underwent initial shockwave lithotripsy 21.2% had a second surgery (shockwave lithotripsy or ureteroscopy) within 3 months compared to 10% of patients who underwent initial ureteroscopy (p <0.01). On multivariable analysis, patients who underwent initial shockwave lithotripsy were more than twice as likely (OR 2.4, 95% CI 2.3–2.5) to undergo a second procedure within 3 months. Older patients were also more likely to undergo a second surgery, while African Americans, Hispanics, uninsured patients and patients with more comorbidities had decreased odds of undergoing a second surgery (all p <0.05). The per patient cost of the initial procedure plus re-treatment at the 3-month mark was $6, 239 for initial shockwave lithotripsy and $5, 319 for initial ureteroscopy (p <0.01). Conclusions: Patients undergoing shockwave lithotripsy are more likely than those undergoing ureteroscopy to have additional stone procedures, making shockwave lithotripsy a more expensive intervention.